STEM department chairs’ perspectives on navigating teaching culture to influence instructional change: a four-frames model analysis - Couch, Brian A.; Prevost, Luanna B.; Stains, Marilyne; Marcy, Ariel E.; Whitt, Blake; Hammerman, James K. L.; Spiegel, Amy N. (Frontiers in Education, 2024)
Academic departments have been highlighted as key targets to sustainably transform the learning environments of postsecondary science, technology, engineering, and mathematics (STEM) courses in the United States. Despite STEM department chairs playing a critical role in shaping their unit, few studies have characterized how chairs view the teaching culture within their department and how cultural features influence instructional change. This study addressed this gap by applying the fourframes model for organizational change to analyze interviews conducted with 14 STEM department chairs at one research-intensive institution in the United States. The department chairs identified several challenges to supporting and advancing teaching culture. These challenges were mostly related to the structures and symbols frames and included the institutional emphasis on research over teaching, inadequate methods to evaluate effective teaching, and the weak teaching feedback mechanism available to faculty. The chairs also described how they leverage their power to affect people and thereby influence the teaching culture. For example, they strategically position teaching as an important aspect of the departmental culture during hiring processes and elevate certain groups of faculty who have demonstrated interest and efficacy in teaching. This study contributes to the literature by providing a rich description of the teaching culture in STEM departments at a research-intensive institution from the perspective of department chairs. This unique focus on department chairs helps identify opportunities for instructional reforms that are grounded in the reality of the departmental environment and provides a framework for considering how change might occur in STEM departments at research-intensive institutions. The opportunities identified emphasize the importance for department chairs to consider and leverage all four frames to enact instructional change.